Pengaruh Kerja Sama Orang Tua Siswa Dengan Guru Terhadap Pendidikan Agama Islam Di MTS Muhammadiyah 03 Sedayulawas Lamongan - Maftuhah (STIT Muhammadiyah Paciran Lamongan, 2020)
Abstract: The purpose of this study is to determine whether there is an effect of cooperation between parents and teachers on Islamic religious education at MTs Muhammadiyah 03 Sedayulawas Lamongan. This research is a qualitative research with a background at MTs Muhammadiyah 03 Sedayulawas Lamongan. Data collection was carried out through observation, interviews / interviews, and documentation. This research uses a qualitative descriptive approach, so the presence of researchers in the field is very important. Researchers act directly as instruments and as data collectors from in-depth observations and are actively involved in research. Data in the form of words were obtained from informants,while additional data was in the form of documents. Data analysis is done by examining existing data, then reducing data, presenting data and drawing conclusions and the final stage of data analysis is to validate the data by using the accuracy and persistence of triangulation observations. The results showed: (1) The cooperation of parents and teachers. (2) Efforts to improve Islamic Religious Education. (3) The effect of cooperation between parents and teachers on Islamic Religious Education